Development of a comprehensive, sustained community mental health system in post-earthquake Haiti, 2010–2019. (2020) - Raviola, G.; Rose, A.; Fils-Aimé, J.R.; Thérosmé, T.; Affricot, E.; Valentin, C.; Daimyo, S.; Coleman, S.; Dubuisson, W.; Wilson, J.; Verdeli, H.; Belkin, G.; et al.
Abstract: Between 2010 and 2019 the international health care organization Partners In Health (PIH) and its sister organization Zanmi Lasante (ZL) mounted a long-term response to the 2010 Haiti earthquake, focused on mental health. Over that time, implementing a Theory of Change developed in 2012, the organization successfully developed a comprehensive, sustained community mental health system in Haiti's Central Plateau and Artibonite departments, directly serving a catchment area of 1.5 million people through multiple diagnosis-specific care pathways. The resulting ZL mental health system delivered 28 184 patient visits and served 6305 discrete patients at ZL facilities between January 2016 and September 2019. The experience of developing a system of mental health services in Haiti that currently provides ongoing care to thousands of people serves as a case study in major challenges involved in global mental health delivery. The essential components of the effort to develop and sustain this community mental health system are summarized.